Subjective Well-Being and Relative Deprivation : An Empirical Link - Conchita D'Ambrosio; Joachim R. Frick (Institute for the Study of Labor (IZA), 2004)
This paper explores the relationship between two well-established concepts of measuring individual well-being: the concept of happiness, i.e. self-reported level of satisfaction with income and life, and relative deprivation/satisfaction, i.e. the gaps between the individual's income and the incomes of all individuals richer/poorer than him. Operationalizing both concepts using micro panel data from the German Socio-Economic Panel (SOEP), we provide empirical evidence for subjective well-being depending more on relative satisfaction than on absolute levels of income. This finding holds even after controlling for other influential factors in a multivariate setting.
Keywords: D31; D63; I31; 330; relative deprivation; satisfaction; subjective well-being; SOEP; Lebensqualität; Einkommensverteilung; Schätzung; Deutschland